Analisis Penambahan Serbuk Kayu Sebagai Kayu Sebagai Pengganti Terhadap Agregat Halus - Widiatmoko, Paskalis Aprilio (Reinforcement Review in Civil Engineering Studies and Management, 2023)
This study aims to analyze the impact of adding sawdust as a substitute for fine aggregate in concrete mixes, with percentage variations of 1%, 1.5%, and 2%. The experiments involved the preparation of concrete mixtures with specific proportions according to each sawdust variation, and the formation of cylindrical concrete samples with a size of 15 cm x 30 cm. A total of 12 cylindrical specimens were prepared for each variation, ensuring representativeness and reliability of the results. Subsequently, mechanical properties of the concrete were tested, including compressive strength, resistance to compressive load, and resistance to deformation. The expected compressive strength plan was 16.9 MPa, but the test results showed a decrease in concrete at 1% by 11.99 MPa, at 1.5% by 7.14 MPa, and at 2% by 5.65 MPa. Analysis of these results provides a focal point for planning strategies to improve the performance of concrete with sawdust and ensure that its use does not compromise critical compressive strength. The findings of this study are expected to provide guidance for the construction industry in integrating alternative, more environmentally friendly materials into daily construction practices.